Expanding a successful community-based obesity prevention approach into new communities: Challenges and achievements. Issue 2 (March 2016) - Bolton, Kristy A.; Kremer, Peter; Gibbs, Lisa; Swinburn, Boyd; Waters, Elizabeth; de Silva, Andrea
Summary: Objective: A previously successful community-based obesity prevention intervention with a focus on school settings was expanded into new communities with varying contexts. In order to understand the complexities involved in implementing health promotion activities in schools, this study examined experiences of school staff and project officers including barriers, contextual factors and achievements. Methods: School environment assessments were conducted in schools across four Victorian communities with school staff ( n = 1–5 staff plus a trained researcher per group in 9 primary and 8 secondary schools) 12–18 months post-intervention. Process reports from project officers were also reviewed and analysed ( n = 4). Results: School staff commonly reported time pressures as a barrier to implementation and project officers working within schools reported competing priorities and limited health promotion experience of staff; lack of stakeholder engagement; low participation in some activities and insufficient implementation time. Contextual factors included community socioeconomic status, student ethnicity and living rurally. Achievements included student and staff enjoyment from programme activities, staff capacity building, partnerships, embedding activities into existing infrastructure and programmes, and having consistent health-related messages repeated through a variety of strategies. Conclusions: Community-based interventions with a focus on school settings need to consider system level, organisational and contextual (i.e. socioeconomic, ethnicity, family and town characteristics) factors when expanding previously effective strategies into new communities. Implementation benefits may have added whole of school benefits in addition to child health. Focussing on overcoming the challenges experienced in this complex initiative is required for future interventions. Trial registration: ACTRN12609000892213.